Efeitos da mobilização precoce em pacientes com sepse internados na unidade de terapia intensiva - Oliveira, Danielle Cristina Alves de (2019)
The aim of this study was to evaluate the muscular strength and concentrations of oxidative and inflammatory markers of sepsis patients admitted to an Intensive Care Unit (ICU) before and after an intervention using an exercise protocol, as well as to analyze the effects of mobilization in these patients. This research was performed at the ICU of Hospital de Clínicas de Uberlândia. Eighteen patients were randomly assigned to the intervention group (GI), who underwent an early mobilization protocol containing electrostimulation, cycloergometer and kinesiotherapy, and 10 in the control group (CG) who received conventional physiotherapy by ICU staff. The interventions were performed for seven days and blood samples were collected for comparison of levels of interleukin-1, tumor necrosis factor-alpha, total antioxidant capacity, carbonylation and malondialdehyde before and after the exercise protocol. As a result, the CG presented a higher mean age and time of sedation. GI presented higher levels of initial lactate and procalcitonin, which may be assumed to be more severe patients. As for interleukin-1 and tumor necrosis factor-alpha, the groups did not present statistical difference in the pre- and post-intervention moments. Regarding oxidative stress analyzes, GI post-intervention presented a significant reduction in the levels of malondialdehyde and carbonylation, however there was no difference in the levels of total antioxidant capacity. The patients submitted to the protocol had a higher final Medical Research Council (MRC) compared to control group, without statistical difference. It can be concluded that a mobilization that can be used to reduce oxidative stress is a group of patients who may have suffered a maintenance mortgage or loss of strength.